The Rho GTPase RhoB regulates cadherin expression and epithelial cell-cell interaction - Vega, Francisco M (Cell Commun Signal, 2015)
BACKGROUND: The Rho GTPase RhoB has been proposed to be a tumor suppressor in cancer and is downregulated in various tumors including prostate. RhoB has different effects on cell migration depending on the cell type and conditions, but the molecular basis for this variability is unclear. RhoB regulates trafficking of membrane receptors and integrins. We have previously shown that RhoB depletion alters focal adhesion dynamics and reduces surface levels of β1 integrin in PC3 prostate cancer cells, correlating with increased migration speed. RESULTS: Here we show that RhoB depletion reduces cell-cell adhesion and downregulates E-cadherin levels as well as increasing internalized E-cadherin in DU145 prostate cancer cells. This is accompanied by increased migration speed. RhoB localizes to cell-cell junctions together with E-cadherin in DU145 cells. RhoB depletion also reduces N-cadherin levels in PC3 cells, which do not express E-cadherin. CONCLUSIONS: These results indicate that RhoB alters migration of cells with cell-cell adhesions by regulating cadherin levels. We propose that the relative contribution of integrins and cadherins to cell migration underlies the variable involvement for RhoB in this process and that the downregulation of RhoB in some epithelial cancers could contribute to the weakening of epithelial cell-cell junction during tumor progression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12964-015-0085-y) contains supplementary material, which is available to authorized users.